1988
DOI: 10.1257/jep.2.1.191
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies: The Winner's Curse

Abstract: Next time that you find yourself a little short of cash for lunch, try the following experiment in your class. Take a jar and fill it with coins, noting the total value of the coins. Now auction off the jar to your class (offering to pay the winning bidder in bills to control for penny aversion). Chances are very high that the following results will be obtained: (1) the average bid will be significantly less than the value of the coins (bidders are risk averse); (2) the winning bid will exceed the value of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
185
0
22

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 463 publications
(210 citation statements)
references
References 15 publications
3
185
0
22
Order By: Relevance
“…value is likely to overpay (for a review see Richard H. Thaler, 1988). 7,8 False consensus suggests that teams will overestimate the need to trade-up in order to acquire a player they value because they will believe, unduly, that other teams value him similarly (L. Ross et al, 1977).…”
Section: Research Hypothesismentioning
confidence: 99%
“…value is likely to overpay (for a review see Richard H. Thaler, 1988). 7,8 False consensus suggests that teams will overestimate the need to trade-up in order to acquire a player they value because they will believe, unduly, that other teams value him similarly (L. Ross et al, 1977).…”
Section: Research Hypothesismentioning
confidence: 99%
“…2 In economics, the 'winner's curse' is the phenomenon where the winning bidder systematically pays an inflated price, or receives a lower than expected profit, in common value auctions (Thaler, 1988). 3 Over 90% of submitted research manuscripts are rejected by the top medical and economic journals 4 Ioannidis (2005) found that nearly a third of the most highly cited medical research studies (those with more than 1,000 citations) are contradicted by or found to have stronger effects than subsequent research published within a few years.…”
mentioning
confidence: 99%
“…Sunstein (1999) explores the idea of preference reversals, originating from Thaler's (1992) work, that proved individuals make different decisions under different circumstances given the same data, as in a different context they view the information as different when, rationally, it should be regarded as giving an identical message. This is because different framing effects may be applied in different decision-making contexts, but to the same information.…”
Section: The Way Forward -The Case For Behavioural Economics In Educamentioning
confidence: 99%